Sub-registro de acidentes do trabalho em localidade do Estado de São Paulo, 1997 - Binder, Maria Cecília Pereira [UNESP]; Cordeiro, Ricardo [UNESP] (Universidade de São Paulo (USP), Faculdade de Saúde Pública, 2003)
OBJETIVO: Estimar o número de acidentes do trabalho ocorridos em determinada localidade e intervalo de tempo e a extensão do sub-registro de casos. MÉTODOS: Amostraram-se 4.782 domicílios residenciais do município de Botucatu, SP, contendo 17.219 moradores, em primeiro de julho de 1997. em cada um dos domicílios, um morador adulto era entrevistado para identificar ocorrência de acidentes do trabalho nos três meses precedentes à entrevista. Nos casos positivos, os acidentados foram entrevistados. Para cálculo do intervalo de confiança utilizou-se a formula de Cochran. RESULTADOS: Confirmaram ter sofrido acidente do trabalho 76 indivíduos, estimando-se em 1.810 o número desses eventos em Botucatu no ano de 1997 e a proporção de incidência em 4,1% (IC95% 3,0%-5,3%). Dos 76 acidentados, 39 não eram cobertos pelo seguro acidente previdenciário (51,3% IC95% 41,1%-61,6%), não se enquadrando na obrigatoriedade de emissão de Comunicação de Acidente do Trabalho (funcionários públicos estatutários, autônomos, assalariados sem registro em carteira, proprietários e outros). Dentre os 37 casos com obrigatoriedade de emissão desse documento, 20 casos não possuíam (54,1% IC39,4%-68,7%). Houve maior proporção de sub-registro de casos em trabalhadores de micro, pequenas e médias empresas, do que entre grandes empresas. Apenas 22,4% (IC13,8%, 30,9%) dos acidentes do trabalho informados nas entrevistas domiciliares foram captados pelos registros previdenciários CONCLUSÕES: Os achados indicam a necessidade de melhoria de utilização de outras fontes de informação, além das Comunicações de Acidentes do Trabalho, para elaboração das estatísticas oficiais sobre acidentes do trabalho.

OBJECTIVES: To estimate the number of occupational accidents that occurred in a certain municipality during a specific period of time as well as the extent of sub-registration. METHODS: The study sample was comprised of 4.782 households within the municipality of Botucatu, São Paulo occupied by a total 17,219 inhabitants on the 1st of July, 1997. In each household, an adult inhabitant was interviewed in order to identify the occurrence of occupational accidents in the three months preceding the interview. When such occurrences were identified, the injured workers were interviewed. The Cochran formula was utilized to calculate the confidence interval. RESULTS: Seventy-six individuals confirmed that they had suffered occupational accidents during these three months. In 1997, there were approximately 1,810 occupational accidents in Botucatu, according to our estimates, and the incidence of work related injuries in the population was approximately 4.1% (CI 95% 3.0%-5.3%). Thirty-nine (51.3%, CI 95% 41.1%61.6%) of the above 76 workers were not covered by the Social Security System. Consequently, their injuries were not reported for there was no legally binding obligation to fill out and emit the official registration form - Comunicação de Acidente do Trabalho (CAT) [the work injury report]. Included among the latter are civil servants and informal sector workers, such as self-employed, casual workers and others. Although the remaining 37 workers (48.7%) were covered by the Social Security System and emission of the work injury report was obligatory, 20 of the cases (54.1% CI 95% 39.4%-68.7%) had not been registered. A greater proportion of cases of sub-registration were found among those workers employed in micro, small and medium sized businesses than among those working in large firms. Only 22.4% (CI 13.8%-30.9%) of the occupational accidents reported in this study were registered by the Social Security System. CONCLUSIONS: Research findings confirm that analyses based on the number of officially registered workplace accidents are limited. It highlights the importance of utilizing other sources of data, besides the registration form for occupational accidents used currently by the Social Security System, Comunicação de Acidente do Trabalho or CAT, in order to elaborate official statistics on occupational accidents.
Under registration of occupational accidents in Brazil, 1997
Keywords: Acidentes de trabalho; Epidemiologia; Sub-registro; Notificação de acidentes de trabalho; Accidents; Epidemiology; Underregistration; Occupational accidents registry